Single arm approach for transcatheter aortic valve implantation - Sacha, Jerzy; Krawczyk, Krzysztof; Gwóźdź, Witold; Gawroński, Radosław (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2021)
The fully percutaneous femoral approach for transcatheter aortic valve implantation (TAVI) is now the gold standard for enabling early patient ambulation. However, an alternative route through the subclavian-axillary access may offer some advantages for rapid mobilization. We present the TAVI technique performed only with the single-arm approach, i.e. in a way that brings us closer to the standards of coronary procedures through radial access.